Efektivitas Model Pendampingan Guru Pembina Pramuka dalam Penguatan Moderasi Beragama di Sekolah Menengah Pertama - Ahmad Misbah; Bahru Rozi; M Robi’in; Welly Kuswanto (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The mentoring program for Scout instructors at SMPN 1 Sukapura, Probolinggo, was implemented to strengthen the integration of religious moderation values into extracurricular activities as part of character development that promotes tolerance and national insight. The main issue identified was the limited understanding and managerial skills of Scout instructors in designing activities aligned with moderation principles. This program applied an integrative mentoring model consisting of preparation, implementation, and reflective evaluation stages. Data were collected through observations, interviews, and questionnaires involving two Scout instructors and thirty participating students. The results indicate a significant improvement in instructors’ ability to design moderation-based Scout activities, achieving an average competency score of 85%. Students also showed increased tolerance, social responsibility, and collaborative attitudes. The mentoring model proved effective for internalizing moderation values through school nonformal activities. The program recommends applying similar models in other schools and developing further studies on moderation-based Scout training.